1997
DOI: 10.1136/bmj.315.7100.85
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of oestrogen replacement therapy and risk of cervical cancer

Abstract: Objective: To examine any possible links between exposure to DDE (1,1-dichloro-2,2-bis (p-chlorophenyl)ethylene), the persistent metabolite of the pesticide dicophane (DDT), and breast cancer. Design: Multicentre study of exposure to DDE by measurement of adipose tissue aspirated from the buttocks. Laboratory measurements were conducted in a single laboratory. Additional data on risk factors for breast cancer were obtained by standard questionnaires. Setting: Centres in Germany, the Netherlands, Northern Irela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 17 publications
2
13
0
1
Order By: Relevance
“…In postmenopausal women, on hormone replacement therapy for menopausal symptoms, irregular periods, or disease prevention, we did not find a significant association. Some authors found that short-term use of hormone replacement therapy suggested an increased risk of HPV detection [Smith et al, 1997] but estrogen replacement therapy did not seem to increase the risk of cervical cancer [Parazzini et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…In postmenopausal women, on hormone replacement therapy for menopausal symptoms, irregular periods, or disease prevention, we did not find a significant association. Some authors found that short-term use of hormone replacement therapy suggested an increased risk of HPV detection [Smith et al, 1997] but estrogen replacement therapy did not seem to increase the risk of cervical cancer [Parazzini et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…A published study was included in this analysis if (i) it contained information on both cases and controls, (ii) there was no matching by a measure of education or income and (iii) the odds ratio (OR) for some indicator of social class was presented or could be derived. All these studies were reviewed and 76 case‐control studies were identified, which presented some information on socio‐demographic characteristics 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78. Of these, 57 studies included information on level of education, 26 included information on income status, 20 utilised a combined social class indicator using several variables ( e.g ., education and income), 5 gave information on husband's level of education, 3 provided information on the number of household commodities ( e.g ., T.V., fridge) and 2 provided information on pay status for healthcare.…”
Section: Methodsmentioning
confidence: 99%
“…HRT has also anticancer capacities at other tumor sites out of the upper aerodigestive tract, such as in stomach, colon, liver, and cervix [71,76,86], which can hardly be explained by a local defense mechanism against tobacco products and exogenous carcinogenic agents. HRT probably exerts this advantageous effect by means of its systemic metabolic and hormonal pathways.…”
Section: Controversial Associations Of Hormone Replacement Therapy Anmentioning
confidence: 98%
“…Unexplained, beneficial anticancer effects of HRT use were reported against oral, esophageal, gastric, colorectal, cervical, liver, and lung cancers [12,71,[74][75][76][77] and there are also contradictory results concerning the associations of HRT and highly hormone-dependent cancers [22,78,79].…”
Section: Controversial Associations Of Hormone Replacement Therapy Anmentioning
confidence: 99%